3D Geological modelling and gravity inversion of a structurally complex carbonate area: application for karstified massif localization. (23rd February 2018) - Husson, Eglantine; Guillen, Antonio; Séranne, Michel; Courrioux, Gabriel; Couëffé, Renaud
Abstract: This paper proposes a new methodology to improve the location of potential karstified areas by gravity inversion of a 3D geological model. A geological 3D model is built from surface observations, 2D seismic reflection profiles and well data. The reliability of this geological 3D model obtained from integration, interpretation and interpolation of such data is first tested against the structural consistency of the model. Its theoretical gravimetric response is compared to gravity field during the forward problem in order to evaluate the validity/robustness of the geological model. The coherency between the gravity field and the gravimetric response is tested. The litho‐inversion modelling quantifies the distribution of rock density in a probabilistic way, taking into account the geology and physical properties of rocks, while respecting the geological structures represented in the 3D model. The result of the inversion process provides a density distribution within carbonate formations that can be discussed in term of karstification distribution. Thus, lower densities correlate with areas that are strongly karstified. Conversely, higher than mean densities are found in carbonate formations mostly located under marly and impervious formations, preserving carbonate from karstification and paleokarstification.